2012
DOI: 10.4269/ajtmh.2012.12-0224
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Use of Water from Community-Scale Water Treatment Refill Kiosks and Childhood Diarrhea in Jakarta

Abstract: Abstract. In developing countries, safe piped drinking water is generally unavailable, and bottled water is unaffordable for most people. Purchasing drinking water from community-scale decentralized water treatment and refill kiosks (referred to as isi ulang depots in Indonesia) is becoming a common alternative. This study investigates the association between diarrhea risk and community-scale water treatment and refill kiosk. We monitored daily diarrhea status and water source for 1,000 children 1-4 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 13 publications
1
32
1
1
Order By: Relevance
“…This fact demonstrates that the possibility of recontamination during transportation or inappropriate cleaning methods of the storage among urban slum dwellers is high. The previous study by Sima et al showed that the usage of water from community-scale water refill stations can reduce the risk of childhood diarrhea [26], but if the quality of refill water is not properly monitored, the community will have risk of consume unstandardized drinking water. Lack of government control on the quality of refill water station production is also an important factor; subsequently, the implementation of an integrated monitoring system for bottled water production is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…This fact demonstrates that the possibility of recontamination during transportation or inappropriate cleaning methods of the storage among urban slum dwellers is high. The previous study by Sima et al showed that the usage of water from community-scale water refill stations can reduce the risk of childhood diarrhea [26], but if the quality of refill water is not properly monitored, the community will have risk of consume unstandardized drinking water. Lack of government control on the quality of refill water station production is also an important factor; subsequently, the implementation of an integrated monitoring system for bottled water production is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Participant selection and data collection are described elsewhere. 19 In brief, study participants were selected from among all age-eligible children registered at public child health centers (Posyandu). Data were collected from children via two methods.…”
Section: Methodsmentioning
confidence: 99%
“…4 Gastrointestinal disease can be transmitted by a number of interdependent environmental factors, which are in turn influenced by socioeconomic factors. 4,11 Water and sanitation risk factors, including inconsistent hand washing, 12,13 access to sanitation, 14 and access to clean drinking water, [15][16][17][18][19][20] have been characterized, in addition to socioeconomic and agerelated risk factors. 4,[21][22][23] Infectious agents for diarrhea differ by transmission route, with different associated disease characteristics likely associated with differing risk-factors and transmission routes.…”
Section: Introductionmentioning
confidence: 99%
“…Decentralized water treatment solutions provide an important alternative to traditional source-based and point-of-use water treatment 14,15. Small-scale systems are decentralized solutions that cater to several families or a small community and, by definition, are smaller than centralized systems 15.…”
Section: Introductionmentioning
confidence: 99%